2004
DOI: 10.1128/mcb.24.22.9752-9762.2004
|View full text |Cite
|
Sign up to set email alerts
|

The TBC (Tre-2/Bub2/Cdc16) Domain Protein TRE17 Regulates Plasma Membrane-Endosomal Trafficking through Activation of Arf6

Abstract: TBC (Tre-2/Bub2/Cdc16) domains are predicted to encode GTPase-activating proteins (GAPs) for Rab family G proteins. While approximately 50 TBC proteins are predicted to exist in humans, little is known about their substrate specificity. Here we show that TRE17 (also called Tre-2 and USP6), a founding member of the TBC family, targets the Arf family GTPase Arf6, which regulates plasma membrane-endosome trafficking. Surprisingly, TRE17 does not function as a GAP for Arf6 but rather promotes its activation in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 67 publications
(99 reference statements)
6
81
0
Order By: Relevance
“…However, USP6 also contains a TBC domain, which binds to the ADP ribosylation 6 (ARF6) GTPase and promotes its activation in vivo independent of its USP domain (37). Recent studies have shown that ARF6 can activate Wnt signaling by stimulating MAPK1/ERK activation and phosphatidylinositide production to promote LRP6 phosphorylation (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, USP6 also contains a TBC domain, which binds to the ADP ribosylation 6 (ARF6) GTPase and promotes its activation in vivo independent of its USP domain (37). Recent studies have shown that ARF6 can activate Wnt signaling by stimulating MAPK1/ERK activation and phosphatidylinositide production to promote LRP6 phosphorylation (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…One obvious, possible mechanism of action for TBC1D3 would be to induce ARF6 activation, similarly to what has been reported for USP6 (Martinu et al, 2004). Thus, we analyzed ARF6-GTP levels in cells overexpressing TBC1D3, or EFA6 or ARF6-Q67L as controls.…”
Section: Tbc1d3 Interacts and Colocalize With Gga3 At The Plasma Membmentioning
confidence: 99%
“…RNTRE regulates clathrin-dependent endocytosis and macropinocytosis by acting as a GAP on RAB5 (Lanzetti et al, 2000(Lanzetti et al, , 2004, and possibly on other RABs (Haas et al, 2005). Conversely, USP6, whose TBC domain is apparently devoid of GAP activity, is involved in the control of plasma membrane-endosomal trafficking in an ARF6-dependent manner (Martinu et al, 2004). Little is known, instead, about TBC1D3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, relevant substrates have not been identified to date. TRE17 has another characteristic domain, the TBC (Tre-2, Bub2, Cdc16) domain, through which it binds to Arf6, a G protein associated with the CIE endosomal membrane system (Martinu et al, 2004). TRE17 colocalizes with Arf6 and CIE cargo proteins.…”
Section: Introductionmentioning
confidence: 99%